Information and communication policy in activity of public authorities (Путеводитель предпринимателя, 2020)
In the article theoretical and organizational aspects of formation of information and communication policy of public authorities are discussed on the example of an activity of the Russian courts. The review of the main media relations technologies, effective in the course of formation of public communications is carried out, conclusions concerning possibility of use of separate instruments of communication management are drawn.